VENEER INDIRECT ALL PORCELAIN SEBAGAI PERAWATAN MULTIPLE DIASTEMA DAN DISKOLORISASI GIGI - Fani Pangabdian; Diana Soesilo; Chandra Sari Kurniawati (Fakultas Kedokteran Gigi UB, 2023)
Background : tooth discoloration and diastema multiple on anterior teeth are very disturbing appearance of a person. Aesthetically it can reduce the patient’s self-confidence, personality and social life. Composite resin can cover tooth discoloration and imperfect tooth shape. However, these restorations have a limited timeframe which reduces their aesthetics. Objective : this case report informs that cases of tooth discoloration and imperfect teeth can be treated with indirect porcelain veneers with long lasting result and superior aesthetics. Methode : A 40-year-old female patient complained of multiple diastema on upper anterior teeth and yellow and dark patches. Patient wants to improve aesthetics with durable materials. Management was carried out by filling in informed consent, B4 color matching, making mock-up models, preparation of porcelain veneers, making temporary veneers directly with composite resins, trial porcelain veneers with variolink composite resin, etching, application of flowable composite resin, checking for occlusion and articulation. Result: discoloration and a corrected anterior dental diastema were seen. No complaints of pain, no complaints percussion, gingiva looked normal, no discoloration on the indirect veneer results (good condition veneer). Conclusion: discoloration and diastema were successfully treated with indirect all porcelain veneers. The patient was very satisfied because his teeth looked tight and had the same color as natural teeth. Keywords: tooth discoloration, indirect veneer, esthetic restoration, multiple diastema, all porcelain